Spatiotemporal patterns of genetic change amongst populations of cassava Bemisia tabaci whiteflies driving virus pandemics in East and Central Africa - Legg, James P.; Sseruwagi, P.; Boniface, S.; Okao-Okuja, G.; Shirima, R.R.; Bigirimana, S.; Gashaka, G.; Herrmann, H.W.; Jeremiah, S.; Ndyetabula, I.; Tata-Hangy, W.K.; Masembe, C.; et al. (Elsevier, 2014)
The greatest current threat to cassava in sub-Saharan Africa, is the continued expansion of plant virus pandemics being driven by super-abundant populations of the whitefly vector, Bemisia tabaci. To track the association of putatively genetically distinct populations of B. tabaci with pandemics of cassava mosaic disease (CMD) and cassava brown streak disease (CBSD), a comprehensive region-wide analysis examined the phylogenetic relationships and population genetics of 642 B. tabaci adults sampled from cassava in six countries of East and Central Africa, between 1997 and 2010, using a mitochondrial DNA cytochrome oxidase I marker (780 bases). Eight phylogenetically distinct groups were identified, including one, designated herein as ‘East Africa 1’ (EA1), not previously described. The three most frequently occurring groups comprised >95% of all samples. Among these, the Sub-Saharan Africa 2 (SSA2) group diverged by c. 8% from two SSA1 sub-groups (SSA1-SG1 and SSA1-SG2), which themselves were 1.9% divergent. During the 14-year study period, the group associated with the CMD pandemic expansion shifted from SSA2 to SSA1-SG1. Population genetics analyses of SSA1, using Tajima's D, Fu's Fs and Rojas’ R2 statistics confirmed a temporal transition in SSA1 populations from neutrally evolving at the outset, to rapidly expanding from 2000 to 2003, then back to populations more at equilibrium after 2004. Based on available evidence, hybrid introgression appears to be the most parsimonious explanation for the switch from SSA2 to SSA1-SG1 in whitefly populations driving cassava virus pandemics in East and Central Africa.